Strategie argumentacji nierzeczowej a etyka dziennikarska. Analiza wybranych wywiadów z politykami przeprowadzonych przez Tomasza Lisa, Monikę Olejnik i Jacka Żakowskiego - Goc, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The aim of this paper is to discuss selected rhetorical strategies applied by journalists during television interviews, as well as to consider whether they demonstrate the professional skills of journalists, or if they should be treated as examples of violating journalistic ethics and standards. The following three interviews have been analyzed in this paper: of Tomasz Lis (with Lech Wałęsa), Monika Olejnik (with Jacek Kurski) and Jacek Żakowski (with Leszek Miller). The author presents the rhetorical strategies used by the journalists and concludes that – as strategies involving the prevention of interlocutors from speaking and presenting their views, misinterpretation of information and journalists’ malevolence – they should be considered incompatible with the ethics of journalism.